The effects of age and other individual factors on radiation induced ESR signals from fingernails - Samayeh Azariasl; Samayeh Azariasl; Samayeh Azariasl; Hiroshi Yasuda; Hiroshi Yasuda (Frontiers in Public Health)
Biodosimetry is crucial for assessing ionizing radiation exposure to guide medical responses. Electron spin resonance (ESR) spectroscopy using fingernails can be effectively used for both occupational and public dose assessments in radiological accidents because of their accessibility and ability to retain stable radiation-induced free radicals. However, despite two decades of research, challenges remain in achieving accurate fingernail dosimetry, mainly owing to the variation in ESR signals among individuals. The purpose of this study was to explore inter-individual differences in ESR signals in fingernails to improve the accuracy and reliability of extremity dosimetry. Fingernail samples were collected from 15 participants (age: 11–64 years), irradiated with X-rays (160 kV, 6.3 mA) at 0, 5, 10, and 20 Gy, and measured using ESR spectroscopy. The effects of individual factors, such as age, sex, health condition, and lifestyle, on radiation-induced ESR signals (RIS) were investigated. Younger participants exhibited stronger RIS intensities and a more linear dose–response relationship. The RIS intensity in female samples tended to be higher than that in male samples. Interestingly, the fingernals of middle-aged donors who regularly took vitamin supplements showed significantly higher ESR signal intensities than those of similar-age donors who did not take supplements. Notable reductions in RIS intensity during storage in a freezer were observed only in older donor samples irradiated at higher doses. These findings underscores the importance of considering age and other individual factors in the calibration for fingernail dosimetry.